Patterns of satellite tagged hen harrier disappearances suggest widespread illegal killing on British grouse moors - Megan Murgatroyd (Nature Portfolio, 2019)
Tackling wildlife crimes requires determining their occurrence and distribution, but they are often difficult to detect. Here, the authors use hen harrier tracking data to show patterns of unexpected tag failure that suggest widespread illegal killing on moors managed for recreational shooting of red grouse.